Evolution of an Electronic Health Record-Based Alert to Optimize Venous Thromboembolism Prophylaxis - Akbashev, Mikhail Y.; Utz, Alyssa; Anjum, Phillip; Watkins, Stacey; Mattaliano, Michael; Patel, Palak; Vigliotti, Debbie; Schenker, Mara L.; Adhyaru, Bhavin B. (Applied Clinical Informatics, 2025)
Venous thromboembolism (VTE) prophylaxis in hospitalized patients must balance risks of bleeding and thrombosis. Clinical changes such as bleeding or renal injury can also trigger changes or delays in thromboprophylaxis. Electronic health record alerts (EHRAs) can allow for targeted notification to providers to improve venous thromboembolism prophylaxis and improve patient outcomes at the risk of alert fatigue if not carefully designed and implemented.This study aimed to develop and refine an EHRA that minimizes nuisance alerts while facilitating appropriate ordering of VTE prophylaxis for medical patients.A multidisciplinary group at a single large safety-net academic medical center developed an EHRA to identify patients at increased thrombosis risk, but without orders for VTE prophylaxis. This was refined over four phases: development and validation, initial monitoring and exclusion criteria adjustment, COVID-19-related modifications, and delayed surveillance and modification. Data analysis evaluated criteria including alert frequency, alert action/utilization, and alert duration.The EHRA fired an average of 33.3 times per day across all phases of the study. Phase 1 of EHRA implementation showed significantly increased alerts per patient (6.4 to 43.3 alerts per day, p < 0.01) as well as the percentage of patients with >5 alerts (2.8 to 60.0%, p < 0.01). Modifications in phase 2 and phase 3 increased alert rates without any significant effect on subsequent action taken by a provider. Phase 4 modifications led to a significant reduction in alert frequency (44.1 to 14.9 alerts per day, p < 0.01) coupled with a notable increase in provider action (0.24 to 7.73%, p < 0.01).This multidisciplinary, provider-centered, intervention improved alert appearance, and information needed to guide providers increased provider engagement 32-fold, with a 3-fold decrease in alert frequency. Despite improvements, ongoing monitoring and maintenance of this alert is important.
Keywords: clinical decision support (CDS); venous thromboembolism (VTE); prophylaxis; best practice advisory; electronic health record; electronic health record alert (EHRA)